La construcción naval en la Galicia autonómica (1980-2023) - José Gómez Alén (Cahiers de Civilisation Espagnole Contemporaine)
At the beginning of the eighties, shipbuilding in Galicia was in a deep crisis that had begun in the second half of the previous decade as a consequence of the oil crisis of the years 1973-74. This paper deals with the general features that have characterized the transformation process of the naval industry and its social impact in order to face the negative effects and the structural problems that had been dragging on since the seventies. Conditioned by the unstable political context of the Transition with the consolidation of democracy and by the subsequent adaptation to the legal and economic framework of the European Economic Community, the sector would be immersed in a profound restructuring until the end of the 20th century. The changes in the ownership of the shipyards and in their productive orientation, as well as the negative consequences for the employment it had traditionally generated, would give rise to the intense socio-labor conflict that was going to be constant during the transformation process of the naval sector, which would reach some stability at the beginning of the second decade of the 21st century.